Cyclic diazo compounds in the construction of spirocyclic scaffolds. (5th January 2021) - Solovyev, Igor; Eremeyeva, Maria; Zhukovsky, Daniil; Dar'in, Dmitry; Krasavin, Mikhail
Graphical abstract: Highlights: Spirocycles are emerging privileged motifs for drug discovery. Cyclic diazo compounds serve as a rich source of spirocycles. A large portion of reactions represent variants of cycloaddition. The other half are typical of metal carbenes. Abstract: Spirocycles represent an emerging class of privileged motifs for drug discovery. The versatility of diazo compounds in constructing cyclic frameworks in general makes cyclic diazo compounds a potentially highly prolific source of spirocyclic scaffolds. While the first examples of obtaining a spirocycle from a cyclic diazo compound are dated as far back as 42 years ago, there appears to be a resurgence of novel methodologies based on this premise. The present Digest Article aims to cover the literature on the subject to-date.